Determination des zones agro-ecologiques d'Afrique: travaux et projets du CIPEA - Henricksen, B.L. (1986)
Outlines some of the work being done by ILCA in the field of agroecological zonation and the use of models to predict the effect of environment on pastoral and agricultural systems. Includes plans for future developments and the potential benefits of the work.